2017
DOI: 10.1007/s11250-017-1250-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different dietary inclusion levels of macadamia oil cake on growth performance and carcass characteristics in South African mutton merino lambs

Abstract: Growth performance and carcass characteristics of South African mutton merino fed graded levels of macadamia oil cake were assessed. A total of 60 South African mutton merino lambs were used in the experiment (initial live weight 25.0 ± 0.45 kg). Five diets with different inclusion levels of macadamia oil cake (MOC) were formulated: T1 (0% MOC, control), T2 (5% MOC), T3 (10% MOC), T4 (15% MOC) and T5 (20% MOC). Effects of inclusion level of MOC on average daily gain (ADG) and average daily feed intake (ADFI) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 12 publications
2
5
2
Order By: Relevance
“…Least performance by lambs associated on the 15% MOC diet may be attributed to low ADFI of these animals. However, contrary to our findings, Acheampong-Boateng et al, (2017) reported that MOC inclusion in lamb diets do not affect ADG.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…Least performance by lambs associated on the 15% MOC diet may be attributed to low ADFI of these animals. However, contrary to our findings, Acheampong-Boateng et al, (2017) reported that MOC inclusion in lamb diets do not affect ADG.…”
Section: Resultscontrasting
confidence: 99%
“…However, lambs fed with 10% MOC supplemented diet had significantly (P<0.05) heavier WCM and CCM than the lambs fed 15% MOC and 10% BSC supplemented diets. Acheampong-Boateng et al, (2017/ 2008 reported similar findings when MOC was included in lamb and cattle diets. Similar findings were also reported by Shirima et al, (2014) and Mioc et al, (2007).…”
Section: Carcass Characteristics Of South African Mutton Merino Lambsmentioning
confidence: 68%
See 1 more Smart Citation
“…As a product of this operation the partially defatted cake is obtained (macadamia pressed cake, MPC) with lipid content in the range of 26–52% . Due to this content and the presence of proteins and minerals, authors have proposed its use as animal feeding, that is, feeding chicken, livestock in confinement, and sheep . However, partially defatted cake may be submitted to a second oil extraction, since macadamia oil has high content of oleic acid (40–51%), followed by palmitoleic acid (24–36%) and palmitic acid (8–13%), which makes it a great ingredient for food and cosmetics formulations.…”
Section: Introductionmentioning
confidence: 99%
“…Reports of the use of macadamia (Macadamia integrifolia) residues in the diet of animals are incipient in the literature. Although animal studies suggest toxicity, promising results in animal husbandry have been obtained from its introduction in the diets of broilers (ACHEAMPONG-BOATENG et al, 2016) and cattle (ACHEAMPONG-BOATENG et al, 2017). However, studies of the impacts of macadamia residue on seminal quality are lacking.…”
Section: Introductionmentioning
confidence: 99%